ANALISIS KOMPENSASI DAN DISPLIN KERJA TERHADAP KINERJA KARYAWAN (PT. AHAZ KARYA MANDIRI PALEMBANG) - Kellyn Oktaviana; Masayu Safita; Randi Yopanggi; Shinta Dwi Putri; Fawwaz El-Farobie; Saprida Saprida (Jurnal Ilmiah Mahasiswa Ekonomi Syariah (JIMESHA), 2021)
Compensation is anything that employees receive in return for their work. In addition to remuneration, it can also motivate them to achieve goals and improve work performance for employees. employees of PT. Ahaz Karya Mandiri Palembang works diligently and disciplines. However, there are also some employees of PT. Ahaz Karya Mandiri Palembang who came to work but did not attend in the morning, there were some employees who attended late and did not attend the afternoon within 15 working days, there were employees who had worked for a long time but had not been appointed as permanent employees. To maximize employee discipline of PT. Ahaz Karya Mandiri Palembang, the head of the company gave compensation so that it had an impact on a pleasant work atmosphere so that it would increase enthusiasm in carrying out work.